Epidemiology and molecular typing of an outbreak of tuberculosis in a hostel for homeless men. Issue 2 (1st February 2000) - Kearns, A M; Barrett, A; Marshall, C; Freeman, R; Magee, J G; Bourke, S J; Steward, M
Abstract : Aim —To investigate a possible outbreak of tuberculosis in a hostel for homeless men using IS6110 profiling, a polymerase chain reaction (PCR) based fingerprinting technique. Methods —Eight cases of tuberculosis were diagnosed in residents of the hostel over a period of 28 months. To provide epidemiological data, a heminested inverse PCR (HIP) assay targeting the insertion sequence IS6110 together with its upstream flanking region was used to fingerprint the eight isolates of M tuberculosis under investigation. Results —The HIP technique gave IS6110 profiles which showed that while three isolates were clearly distinct, the remaining five strains were indistinguishable, suggesting the latter were representatives of a single outbreak strain. Conclusions —The HIP assay proved discriminatory and facilitated repeated testing for the direct comparison of strains as more patients presented over the protracted course of this outbreak.